2014
DOI: 10.1111/1467-9477.12031
|View full text |Cite
|
Sign up to set email alerts
|

Do Anti‐immigration Parties Matter? The Case of the Sweden Democrats and Local Refugee Policy

Abstract: With the increased electoral success of anti‐immigration parties, questions regarding what impact the parties actually have naturally follow. Previous research has rarely explored this question. Furthermore, within this body of research, one is given different answers. While some argue that anti‐immigration parties have made an impact on public policy, others find no such evidence. This article shows that some of this inconsistency is a consequence of the methodological strategies that have been employed. Prev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
28
1
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 34 publications
(31 citation statements)
references
References 47 publications
1
28
1
1
Order By: Relevance
“…Group threat theory predicts that a hostile political climate will induce feelings of threat, and thereby influence attitudes towards immigrants (Blumer 1958;Hopkins 2010). While RRPs have been found to impact policy positions of other political parties (Minkenberg 2001;Bolin et al 2014;Careja et al 2016), previous studies provide mixed results in relation to the degree of negative immigrant attitudes (Muis & Immerzeel 2017). While some find significant effects of RRP presence (Semyonov et al 2006; Sprague-Jones 2011), others do not (Dunn & Singh 2011;Bohman & Hjerm 2016), which can be related to how RRPs generally lack legitimacy in the eyes of the broader public (cf.…”
Section: The Country Contextsmentioning
confidence: 99%
“…Group threat theory predicts that a hostile political climate will induce feelings of threat, and thereby influence attitudes towards immigrants (Blumer 1958;Hopkins 2010). While RRPs have been found to impact policy positions of other political parties (Minkenberg 2001;Bolin et al 2014;Careja et al 2016), previous studies provide mixed results in relation to the degree of negative immigrant attitudes (Muis & Immerzeel 2017). While some find significant effects of RRP presence (Semyonov et al 2006; Sprague-Jones 2011), others do not (Dunn & Singh 2011;Bohman & Hjerm 2016), which can be related to how RRPs generally lack legitimacy in the eyes of the broader public (cf.…”
Section: The Country Contextsmentioning
confidence: 99%
“…Only few studies have analyzed the strategies of these parties to achieve policy influence and reach their policy goals. These studies, for good reasons, focused especially on immigration policy (Schain ; Akkerman ; Van Spanje ; Bolin et al ) and multiculturalism (Han ), and found that PRW parties have restrictive effects. This finding is unsurprising, given that these policies touch the parties’ core programmatic issues and affect a well‐defined target group.…”
Section: Introductionmentioning
confidence: 99%
“…In this regard, one study concluded that electoral support for the Sweden Democrats increased in municipalities where mainstream parties took tougher positions on immigration (Dahlström and Sundell 2012). On the other hand, it can be noted that at the level of decisions on refugee reception in Swedish municipalities where SD had political representation, it has not been found that other parties took more restrictive directions concerning refugee policies to counteract the electoral success of SD (Bolin et al 2014).…”
Section: Discussion: Far-right Populist Strategy Inclusionary Rural mentioning
confidence: 99%